Prevalence and Sociodemographic Profile of Anaemia in Pregnancy at a Tertiary Care Center - Anand , Smriti; Gupta , Neena; Diwvedi , Seema; Singh , Neetu; Diwedi , G. N.; Usmani , Fatima (Current Progress in Medicine and Medical Research Vol. 5, 2023)
This chapter highlights to determine the prevalence of anaemia in pregnancy and various associated sociodemographic factors. WHO has accepted up to 11 gm% as the normal haemoglobin level in pregnancy. Therefore any haemoglobin level below 11 gm% in pregnancy should be considered as anaemia. Studies carried out in India and elsewhere have shown that iron deficiency is the major cause of anaemia followed by folate deficiency.Prevalence of anaemia in South Asian countries is among the highest in the world. WHO estimates that even among the South Asian countries, India has the highest prevalence of anaemia. What is even more important is the fact that about half of the global maternal deaths due to anaemia occur in South Asian countries; India contributes to about 80 per cent of the maternal deaths due to anaemia in South Asia.Therefore this study was conducted to study prevalence and associated demographic factors with it. This prospective study was conducted on all anaemic antenatal cases irrespective of gestational age attending the hospital Upper India Sugar Exchange Maternity Hospital, GSVM medical college Kanpur during period Jan 2013 to August 2014. During this period all antenatal patients (4300) who came in outdoor and indoor were included in the study. Prevalence of anaemia among them and its associated sociodemographic factors were studied. The study found the prevalence of anaemia in pregnant females during our study period was 92% of which moderate were 70%,mild 20%,severe 7% & very severe were 3% using WHO criteria as degree of anaemia. Anaemia was more prevalent in early age group because of early marriages & in late age group because of multiple births. Although there are several national nutritional anaemia prevention programmes in India, anaemia still poses a serious threat to mother and foetus during pregnancy by increasing the risk of maternal and perinatal death and morbidity.